(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Concrete is universally the most common building material in Nigeria construction industry but had also been reported as one of the major causes of structural failure. However, in spite of the popularity of concrete structures, if not properly constructed and the quality maintained, it can deteriorate prematurely which is often referred to as our crumbling infrastructure. The study aimed at evaluating strategic measures for effective quality control management of concrete works in Anambra State, Nigeria. A survey research method was adopted for this study. Data was obtained through both primary and secondary sources. The population for this study comprises of registered construction professionals in Anambra state and was surveyed through a well structured questionnaire survey approach. Data generated were analyzed using Tables, Percentage, Ranking and Mean Score. A total of one hundred and fifty eight questionnaires were distributed to registered construction professionals in Anambra State and one hundred and twenty nine questionnaires were returned. The sample size for the study is therefore 129. The findings of the study revealed that quality concept, quality management system, quality control in construction, quality management standard, quality plan, professional regulatory bodies, companies own quality control document, various acts /decrees for construction professionals, the national building code, action to be taken at each stage are all quality control management strategies responsible for ensuring quality concrete works in buildings in the study area. The study also unveiled that quality concept is the most important strategic measure to ensure good quality of concrete elements and that there little or no enforcement from both Government and its Agencies on quality control of concrete elements in buildings industry in the study area. The study recommended that Government agencies, professionals and other key stakeholders need to implement regular inspections of stages of concrete works at building sites; to continuously survey and monitor concrete elements as to detect impending failure and also ensure that every quality control strategy should be covered in the aspect of concrete, provide effective guidance on the project to achieve quality concrete works.